Effects of Short- and Long-Distance Road Transport and Temperament on the Magnitude of β-Endorphin Response in Limousine Bulls - Esterina Fazio; Salvatore Cavaleri; Pietro Medica; Cristina Cravana; Deborah La Fauci (Ruminants)
The purpose of this study was to evaluate the effects of short- and long-distance road transport and temperament on β-endorphin (β-EP) concentrations in 23 Limousine bulls, aged 12 ± 2 months old, taking into account the related effect on body weight (BW) decrease. Animals were transported by road from France to Sicily over a distance of 2200 km in about 33 h. Bulls were divided into calm and reactive subjects based on their exit velocity (EV) measurements taken one week prior to transportation. Blood samples were taken during four different time points: in the morning, immediately before loading in baseline conditions; after the short-distance road transport of 55 km; at their arrival in Sicily after a long-distance road transport of 2200 km; and after 15 days of stabling in finishing and fattening barns, before slaughtering. Animals were weighed before departure, at the arrival in Sicily, and after 15 days. Significant effects of time, temperament, and their interaction were observed for β-EP. It increased after long-distance transport in both groups, but more markedly in calmer bulls, returning to baseline values after 15 days. Significant effects of time were also observed for BW, which decreased after long-distance road transport and restored after 15 days in both groups. The results suggest that long-distance road transport induces a significant increase in the β-endorphin concentrations in Limousine bulls, with the greatest increase in calm subjects.